(untitled) (Research, Society and Development, 2021)
His article aims to discuss and analyze, through an epistemological dialogue with some of the main pedagogical approaches to Physical Education, how didactics and methodology were developed in them (in pedagogical approaches) and after them and what are the objectives of Physical Education in elementary education in these approaches. For this, the text was structured in three sections. In each section we choose a pedagogical approach to: Physical Education to guide the epistemological dialogue. The analyzed approaches are Developmental, Critical-Overcoming and Full Body Education. As a conclusion, we consider that each approach brought some contribution to the field, but none is irreproachable, all have flaws. Recognizing this would have been much more fruitful and beneficial for the development of Physical Education than the trend of ideological dispute for the conquest of the hegemony of the countryside.